α7-Acetylcholine receptor antibodies in two patients with Rasmussen encephalitis - Watson, R; Jepson, J; Bermudez, I; Alexander, S; Hart, Y; McKnight, K; Roubertie, A; Fecto, F; Valmier, J; Sattelle, D; Beeson, D; Vincent, A; et al. (2005)
Rasmussen encephalitis (RE) sera were screened for antibodies to human α7 nicotinic acetylcholine receptors (nAChRs) using electrophysiology, calcium imaging, and ligand binding assays. Sera from two of nine patients with RE blocked ACh-induced currents through α7 nAChRs and the ACh-induced rise in intracellular free calcium ([Ca2+]i) and inhibited 125I-α-bungarotoxin binding in cells expressing α7 nAChRs. Thus, the α7 nAChR is a potential target for pathogenic antibodies in patients with RE. Copyright © 2005 by AAN Enterprises, Inc.